Chemo-enzymatic route to bridged homolyxofuranosyl-pyrimidines. (June 2020) - Kumar, Sandeep; Singla, Harbansh; Maity, Jyotirmoy; Mangla, Priyanka; Prasad, Ashok K.
Abstract: Synthesis of 2′- O, 5′- C -bridged- β -d -homolyxofuranosyl nucleosides U and T have been achieved starting from diacetone-d -glucose in overall yields 55.7 and 57.1%, respectively. Quantitative regioselective monoacetylation of the lone primary hydroxyl group in trihydroxy nucleoside intermediate, i. e. 3′- O -benzyl- β -d -glucofuranosyl nucleosides mediated by Novozyme®-435 has been utilized as the key step in the synthesis of homolyxofuranosyl nucleosides. The structure of the synthesized 2′- O, 5′- C -bridged- β -d -homolyxofuranosyl uracil and -thymine has been established on the basis of their spectral (IR, 1 H, 13 C NMR and HRMS) data analysis and the structure of earlier nucleoside was confirmed by its X-rays diffraction analysis which revealed that these 2′- O, 5′- C -bridged homo-nucleosides are locked into S -type sugar puckering. Graphical abstract: Image 1 Highlights: 2′- O, 5′- C -Bridged- β -d -homolyxofuranosyl nucleosides U and T have been synthesized. X-rays diffraction analysis revealed that 2′- O, 5′- C -bridged homo-nucleosides are locked into S -type sugar puckering. Environment friendly regioselective monoacetylation carried out by Novozyme®-435. Overall yields for synthesis of nucleosides U and T, starting from diacetone-D-glucose are 55.7 and 57.1%, respectively.